2015
DOI: 10.3390/molecules20059405
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Structural Changes in Candida albicans Caused by the Hydroalcoholic Extract from Sapindus saponaria L.

Abstract: Vulvovaginal candidiasis (VVC) is a disease caused by the abnormal growth of yeast-like fungi in the mucosa of the female genital tract. Candida albicans is the principal etiological agent involved in VVC, but reports have shown an increase in the prevalence of Candida non-C. albicans (CNCA) cases, which complicates VVC treatment because CNCA does not respond well to antifungal therapy. Our group has reported the in vitro antifungal activity of extracts from Sapindus saponaria L. The present study used scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
3
9
0
1
Order By: Relevance
“…The MIC and minimum fungicidal concentration (MFC) values of ETHOSS were comparable, suggesting that it has an efficient fungicidal action, which concurs with previous findings [ 12 , 16 ]. In fact, ETHOSS causes changes in the fungal membrane and cell wall in the first instance of contact, causing cell lysis [ 19 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The MIC and minimum fungicidal concentration (MFC) values of ETHOSS were comparable, suggesting that it has an efficient fungicidal action, which concurs with previous findings [ 12 , 16 ]. In fact, ETHOSS causes changes in the fungal membrane and cell wall in the first instance of contact, causing cell lysis [ 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…Phytochemical characterization of the ethanolic fraction of the crude extract of S. saponaria identified compounds with antifungal properties. The ESI-MS spectrum of the ETHOSS detected the typical saponin peaks ( Figure 1 ), similar to those reported in a previous study [ 16 ]. For saponins peaks in the range of 650–1000 m/z, the highest intensities were seen in the peaks of 683.27, 881.50, 923.48, and 965.58 m/z.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Ultrathin sections were compared in a solution of 2.0% uranyl acetate and lead nitrate/acetate. Samples was examined under a JEOL 1200EX II transmission electron microscope (Peabody, MA, USA) [34].…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…[ 53 ] However, ample number of research findings indicates that many medicinal plants can play cytoprotective role. [ 10 51 54 ] Sarkar et al . showed that methanolic extract of C. crista showed protection against Fe(2+)-mediated oxidative DNA damage.…”
Section: Discussionmentioning
confidence: 99%